STABLE LAWS - Sudarno
Abstract : In this thesis we discuss about the stable laws of the random variables. The form of the stable laws has a normal distribution or the characteristic function which have fixed conditions. The computation of the stable characteristic funtions are the tangen function if the exponent is between 0 to 2 but not 1 and the logaritm function if the exponent is 1. The necessary and sufficient condition for a distribution function to be in the domain of attraction of a stable law is also consider.